CARBOTHERMAL REDUCTION PROCESS OF MILLED AMORPHOUS SILICON DIOXIDE USING TAGUCHI’S METHOD - NANDA KUMAR, KISHEN (IRC, 2017)
In today's era of cutting edge technology of the highly competitive engineering advancement, silicon carbide (SiC) material will be the workhorse of power electronics and thermo-mechanical industry. The apprehension behind this is because it's astounding properties which includes great durability, rigidity, resistance against corrosion and wear in high temperatures. Also, SiC can manage the same level of power at half the size, enabling impressive increase in power together with reliability. This study concerns the carbothermal reduction of milled amorphous silicon dioxide (SiO2) to produce SiC using Taguchi's Design Matrix. The major problem faced by industrially manufactured SiC is that, it's often synthesized at elevated temperature in electrical resistance furnace which required further milling and purification process as they possessed large grains which is a critical issue. Manufacturers also have no precise configuration to synthesis maximum yield of SiC from amorphous SiO2 in carbothermal reduction. Therefore, the primary objective of this research is to have an imperative understanding on the effects of parameters for optimal production of SiC. As for such, the response of four operation specifications; mechanical milling duration, time, heating rate and temperature, on amorphous SiO2 was analysed via nine experiment of carbothermal reduction. The morphology changes of amorphous SiO2 to SiC whiskers formation was reviewed using Scanning Electron Microscope (SEM) and phase analysis with X-Ray Diffraction (XRD). The response data was then evaluated by employment of the Analysis of Variance (ANOVA) technique and the end results was used to establish a design model devolved by the Design-Expert software to understand the significance of each parameter on SiC response rate.